2020
DOI: 10.5194/acp-2019-1120
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Worsening urban ozone pollution in China from 2013 to 2017 – Part 1: The complex and varying roles of meteorology

Abstract: Abstract. China has suffered from increasing levels of ozone pollution in urban areas despite the implementation of various stringent emission reduction measures since 2013. In this study, we conducted numerical experiments with an up-to-date regional chemical transport model to assess the contribution of the changes in meteorological conditions and anthropogenic emissions to the summer ozone level from 2013 to 2017 in various regions of China. The model can faithfully reproduce the observed meteorological par… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The heterogeneous reactions in the original CMAQ model (version 5.2.1) includes only uptakes of NO2, NO3, and N2O5 on aerosol surfaces. To faithfully reproduce the effect of aerosols on O3 via scavenging gaseous pollutants, we updated the 105 heterogeneous reaction rate of NO2 and NO3 on the aerosol surface and incorporated additional heterogeneous reactions of gases into the CMAQ model, namely the uptakes of HO2, O3, OH, and H2O2 (refer to Table S2 in the companion paper (Liu and Wang, 2020) for the detailed heterogeneous reactions in the original and updated CMAQ models). The uptake coefficients (γ) of gases are the key parameters of heterogeneous reactions, but they vary according to factors such as aerosol water content and aerosol composition.…”
Section: Updating Heterogeneous Reactionsmentioning
confidence: 99%
See 3 more Smart Citations
“…The heterogeneous reactions in the original CMAQ model (version 5.2.1) includes only uptakes of NO2, NO3, and N2O5 on aerosol surfaces. To faithfully reproduce the effect of aerosols on O3 via scavenging gaseous pollutants, we updated the 105 heterogeneous reaction rate of NO2 and NO3 on the aerosol surface and incorporated additional heterogeneous reactions of gases into the CMAQ model, namely the uptakes of HO2, O3, OH, and H2O2 (refer to Table S2 in the companion paper (Liu and Wang, 2020) for the detailed heterogeneous reactions in the original and updated CMAQ models). The uptake coefficients (γ) of gases are the key parameters of heterogeneous reactions, but they vary according to factors such as aerosol water content and aerosol composition.…”
Section: Updating Heterogeneous Reactionsmentioning
confidence: 99%
“…The shipping emissions were kept unchanged in the 5-year simulation, due to a lack of data for recent years. In Part 1 of our work (Liu and Wang, 2020), we showed the effect of changes in total anthropogenic 150 emission on O3 changes by comparing the O3 concentrations in 2013 simulated using anthropogenic emissions from different years. In this study, three additional sets of modeling experiments were established.…”
Section: Experiments Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies showed an O 3 increase in cities, e.g. maximum daily 8-hour average O 3 concentrations increased by on average 0.46 ppb per year in 74 cities across China from 2013 to 2017 (Liu et al, 2018;Liu and Wang, 2020). The ground-level O 3 is considered one of the most harmful air pollutants in terms of effects on human health (e.g.…”
Section: Introductionmentioning
confidence: 99%